2016
DOI: 10.1515/jpem-2013-0474
|View full text |Cite
|
Sign up to set email alerts
|

Markers of bone metabolism, serum leptin levels and bone mineral density in preterm babies

Abstract: Abstract:The prospective study assessed the influence of serum leptin levels on markers of bone metabolism and bone mineral density in 2-year-old infants born preterm. A total of 57 randomized preterm Caucasian newborns (32nd-37th week of gestation) were included in the study. Bone metabolism markers were measured every 6 months. The infants were monitored prospectively up to the age of 2 years. When the infants turned 2 years of age, they were investigated by dual energy X-ray absorptiometry (lumbar spine). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The development of adipose tissue in preterm infants may be delayed compared with in term infants, potentially resulting in leptin deficiency. Veselá et al (28) reported that the median cord blood concentration of leptin was 3.07 µg/l and the median cord blood concentration of leptin in infants at 32-33 weeks' gestation was 2.89 µg/l, which was lower than the 3.13 µg/l observed in preterm infants at 34-36 weeks' gestation. Nagasaki and Ohta (29) revealed that the median serum concentration of leptin at 33-38 weeks' gestation was 2.3 ng/ml (range: 1.0-3.9 ng/ml).…”
Section: Effects Of Leptin On Neurocognitive and Motor Functions In Jmentioning
confidence: 89%
“…The development of adipose tissue in preterm infants may be delayed compared with in term infants, potentially resulting in leptin deficiency. Veselá et al (28) reported that the median cord blood concentration of leptin was 3.07 µg/l and the median cord blood concentration of leptin in infants at 32-33 weeks' gestation was 2.89 µg/l, which was lower than the 3.13 µg/l observed in preterm infants at 34-36 weeks' gestation. Nagasaki and Ohta (29) revealed that the median serum concentration of leptin at 33-38 weeks' gestation was 2.3 ng/ml (range: 1.0-3.9 ng/ml).…”
Section: Effects Of Leptin On Neurocognitive and Motor Functions In Jmentioning
confidence: 89%
“…Data on this association in children are scarce, and current literature is inconclusive, with studies reporting positive, negative or no associations . In children born preterm (between 32 and 37 weeks of gestation), no relation was found between cord blood leptin and lumbar spine BMD at the age of 2 years . To our knowledge, no studies have investigated associations between leptin and bone metabolism in children born before 32 weeks of gestation.…”
Section: Introductionmentioning
confidence: 88%
“…Like adiponectin, lower leptin levels were detected in premature infants at birth, with greater decreases in relation to lower GA [46]. However, this correlation may become inverted when levels are analyzed at later ages, probably influenced by the growth pattern and an increase in BMI [53] and the amount of fat mass [54].…”
Section: Discussionmentioning
confidence: 96%
“…Adipokines values may also differ by perinatal factors, such as weight and GA at birth [44,45]. Lower values of adiponectin, leptin and resistin were reported in infants born preterm [44,46], and in those small for gestational age [44,45], compared with full-term infants and newborns adequate for gestational age (AGA). However, adipokine research beyond birth in premature children and its link to early postnatal growth is scarce and controversial.…”
Section: Discussionmentioning
confidence: 99%